Evaluating the effectiveness of vitamin D supplementation with Liv-52 in Wistar rats on carbontetrachloride-induced liver disease: Effects on lipid peroxidation and lipid profiles - Karunakaran Ponnazhagan, Bukkaraju Sumanth Kumar, Ursula Sampson (Journal of Applied Pharmaceutical Science, 2024)
The objective is to study the impact of vitamin D in supplementation with Liv-52 on lipid peroxidation (LPO) and lipid profile in hepatic disease caused by carbon tetrachloride (CCl4). The study involved dividing the animals into six different groups, each containing six animals. The first group is referred to as the control group (Group I). Male Wistar rats were administered CCl4 (1 ml/kg, b.w) twice a week for weeks (Group II), vitamin D (500 IU/kg, b.w) (Group III), and Liv-52 (1 ml/kg, b.w) (Group IV) and combination of both (Group V) were treated orally for 9 weeks, and group VI animals were treated with a combination of vitamin D and Liv-52 without hepatotoxin. The effects of this combination on LPO and lipid profile parameters [total cholesterol, triglyceride (TGL), high-density lipoprotein (HDL), and very low-density lipoprotein (VLDL)] were measured in the serum samples. The results showed that in the diseased animals, there were increased levels of total cholesterol, TGL, and VLDL, and decreased levels of HDL compared to control rats. Supplementation with vitamin D and Liv-52 resulted in significantly decreased levels of total cholesterol, TGL, and VLDL, and significantly increased levels of HDL compared to the diseased animals alone. This suggests that the mixture of vitamin D and Liv-52 effectively reduced LPO and improved the lipid profile in liver disease caused by CCl4.
Keywords: Lipid peroxidation, lipid profile, carbon tetrachloride, vitamin D